BRG1 Mediates Nephronectin Activation in Hepatocytes to Promote T Lymphocyte Infiltration in ConA-Induced Hepatitis - Hong, Wenxuan; Kong, Ming; Qi, Mengwen; Bai, Hui; Fan, Zhiwen; Zhang, Ziyu; Sun, Aijun; Fan, Xiangshan; Xu, Yong (Frontiers in Cell and Developmental Biology, 2021)
Concanavalin A (ConA) induced fulminant hepatitis is characterized by massive accumulation of T lymphocytes in the liver. A host of chemoattractive substances are known to promote T cell homing to the liver during acute hepatitis. Here we report that hepatocyte conditional knockout (LKO) of BRG1, a chromatin remodeling protein, mitigated ConA-induced fulminant hepatitis in mice as evidenced by reduced plasma ALT and AST levels as well as hepatocyte necrosis. Consistently, there were fewer T lymphocyte infiltrates in the LKO livers compared to the WT livers paralleling down-regulation of T cell specific cytokines. Further analysis revealed that BRG1 deficiency repressed the expression of several chemokines critical for T cell homing including nephronectin (Npnt). BRG1 knockdown by siRNAs blocked the induction of Npnt in hepatocytes and attenuated T lymphocyte migration in vitro, which was reversed by the addition of recombinant nephronectin. Mechanistically, BRG1 interacted with b-catenin to directly bind to the Npnt promoter and activate Npnt transcription. Importantly, a positive correlation between BRG1 expression and nephronectin expression was detected in human acute hepatitis biopsy specimens. In conclusion, our data identify a novel role for BRG1 as a promoter of T lymphocyte trafficking by activating Npnt transcription in hepatocytes.